MAPPING GENDER-RELATED PROVISIONS IN INDONESIA'S FREE TRADE AGREEMENT - Nurul Aulia; Yulia Rimapradesi; Muhammad Aditya Purnomo; Larassita Damayanti (Intermestic: Journal of International Studies, 2026)
International trade is increasingly recognized as a policy arena that is not gender-neutral.  However, systematic mapping of gender mainstreaming across Indonesia’s trade agreement portfolio remains limited. This study maps the presence and design of gender-related provisions in 19 Indonesian international trade agreements concluded up to 2025. It applies a gender-related provisions framework and assesses five agreements containing explicit provisions using the International Trade Centre instrument across ten dimensions. The study combines document-based content analysis, corpus analysis using AntConc, manual verification, and a staged scoring procedure with triangulation to reach consensus scores. The findings indicate that 14 agreements (74%) are gender-blind, while five agreements (26%) contain explicit gender-related provisions. The Indonesia–Canada CEPA (2025) achieves an Advanced Gender Responsiveness score (85%), while the remaining agreements fall into the Evolving (42.5% and 35%) and Limited (32.5% and 20%) categories. The frequency dimension is most commonly met, whereas the dispute settlement dimension is most frequently absent.